Comparing Dyslipidemia Patterns in Newly Diagnosed and Long-Term Type 2 Diabetics in a Tertiary Care Hospital at Mirpur Khas, Sindh: Dyslipidemia Patterns in Newly Diagnosed and Long-Term Type 2 Diabetics - Ahsan, Naveed; Anique, Muhammad; Shafi, Rubina; Khan, Wajahat Ullah; Alam, Shaista; Noureen, Fakhra (Pakistan Journal of Health Sciences, 2024)
Dyslipidemia is a common metabolic condition linked with type 2 diabetes mellitus and is a substantial risk factor for cardiovascular disease. The pathogenicity and pattern of dyslipidemia may vary with the duration of diabetes, requiring investigation of these changes to improve treatment approaches. Objectives: To compare the prevalence and patterns of dyslipidemia in newly diagnosed compared with long-term type 2 diabetes mellitus patients in a tertiary care hospital in Pakistan. Methods: A comparative cross-sectional study was conducted with 300 type 2 diabetes mellitus patients, divided into two groups: 150 newly diagnosed and 150 long-term diabetics. HbA1c and Lipid profiles (total cholesterol, low-density lipoprotein, high-density lipoprotein, and triglycerides) were assessed. Dyslipidemia was defined per American Diabetes Association guidelines. Statistical analysis was performed using SPSS version 25.0, with a p-value of <0.05 considered significant. Results: The results show that the patients with long-term type 2 diabetes mellitus are associated with significantly increased (92%, p<0.05) levels of lipid profile parameters as compared with the newly diagnosed type 2 diabetes mellitus patients (78%). Moreover, the mean HbA1c levels in blood are positively associated with the severity of dyslipidemia. Conclusion: It was concluded that dyslipidemia progressively increases with the advancement of type 2 diabetes mellitus.